Public Service Integrity and the Quality of Governance: Examining the Role of Citizen-Administrator Value Congruence. (4th May 2019) - Boyd-Swan, Casey H.; Molina, Anthony D.
Abstract : The aim of this study is to examine the role that citizen perceptions of value congruence with public administrators can play in how we measure and evaluate public service integrity, as well as the extent to which such perceptions are associated with how citizens assess the quality of governance. Along those lines, this article reports the results of a pilot study that utilized an original survey, the Citizen-Administrator Value Congruence Survey, in order to measure citizen perceptions of public service value congruence with police officers and examine whether these perceptions are associated with how citizens assess the quality of governance. The findings suggest that perceived value congruence between citizens and police officers is associated with a number of important quality of governance indicators, including increased levels of citizen trust; perceptions of legitimacy; effective communication; positive relationships; and the ability of police officers to advance the public interest.